Behavioral and biological risk factors of non-communicable diseases: Results of a nationally representative cross-sectional survey in Algeria - Karl Peltzer; Djamila Nadir Azirou; Edith Phalane; Mohlago Ablonia Seloka; Refilwe N. Phaswana-Mafuya (Population Medicine)
Introduction There is a need to strengthen the evidence base for context-specific heterogeneities in factors that may potentiate or reduce adverse outcomes of non-communicable disease (NCDs). The study aimed to estimate the prevalence of behavioral and biological risk factors for NCDs among adults in Algeria.